2008
DOI: 10.1590/s0103-84782008000500037
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de contaminação por Staphylococcus e suas enterotoxinas e monitorização das condições de higiene em uma linha de produção de queijo de coalho

Abstract: RESUMO Avaliou-se o perfil de contaminação por Staphylococcus e suas enterotoxinas e monitorou-se as condições de higiene em uma linha de produção de queijo de coalho por meio da técnica de bioluminescência (ATP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 15 publications
0
12
0
13
Order By: Relevance
“…This high CPS concentration could have occurred because this food is susceptible to contamination, particularly during the milking process, from the person performing the operation, from the utensils and equipment used, and even from one animal to another, especially in cases of mastitis in herds (Hait and Bennett, 2012). Borges et al (2008) also found that 100% of the RRM samples from a dairy in Ceará (Brazil) were contaminated by CPS with values between 10 3 and 10 6 CFU/mL. According to Sommerhäuser et al (2003), the microbiological quality of milk is directly related to the hygiene of the milking process.…”
Section: Discussionmentioning
confidence: 99%
“…This high CPS concentration could have occurred because this food is susceptible to contamination, particularly during the milking process, from the person performing the operation, from the utensils and equipment used, and even from one animal to another, especially in cases of mastitis in herds (Hait and Bennett, 2012). Borges et al (2008) also found that 100% of the RRM samples from a dairy in Ceará (Brazil) were contaminated by CPS with values between 10 3 and 10 6 CFU/mL. According to Sommerhäuser et al (2003), the microbiological quality of milk is directly related to the hygiene of the milking process.…”
Section: Discussionmentioning
confidence: 99%
“…Após a verificação da morfologia das colônias, aquelas com características compatíveis com Staphylococcus foram submetidas à coloração pelo método de Gram e confirmação microscópica. Posteriormente, foram realizadas as provas da catalase, para diferenciação do gênero Staphylococcus de Streptococcus, e da DNAse, para diferenciação de S. aureus e SCoN (14) . As colônias que apresentaram características semelhantes às bactérias gram negativas foram submetidas à coloração pelo método de Gram com confirmação microscópica e submetidas a testes complementares, por meio de provas bioquímicas, necessárias para a identificação das colônias suspeitas (TSI, SIM, Citrato de Simmons, Ureia, Lisina) (13) .…”
Section: Methodsunclassified
“…Other studies indicate that the lower quality of the milk used as raw material in dairies may be related to contamination by Staphylococcus spp. (BORGES et al, 2008;LAMAITA et al, 2005). Borelli et al (2006) also confirmed the presence of Staphylococcus spp.…”
Section: Figure 1 Median Maximum and Minimum Values; First And Thimentioning
confidence: 99%